8(3x+2)-2x=5+12x-9

Simple and best practice solution for 8(3x+2)-2x=5+12x-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(3x+2)-2x=5+12x-9 equation:



8(3x+2)-2x=5+12x-9
We move all terms to the left:
8(3x+2)-2x-(5+12x-9)=0
We add all the numbers together, and all the variables
8(3x+2)-2x-(12x-4)=0
We add all the numbers together, and all the variables
-2x+8(3x+2)-(12x-4)=0
We multiply parentheses
-2x+24x-(12x-4)+16=0
We get rid of parentheses
-2x+24x-12x+4+16=0
We add all the numbers together, and all the variables
10x+20=0
We move all terms containing x to the left, all other terms to the right
10x=-20
x=-20/10
x=-2

See similar equations:

| j3=2.08 | | 4(v-1)+7=5(2v-3 | | 6k+2(5k-2)=12 | | -3x-3=-8(6+6x | | (2x–3)(2x-3)=0 | | -55=-19+9f | | p+4/3=-10 | | 3/4x+1/2=8 | | 1/2(4y-6)=2+7y | | 5x+9+21=180 | | 2(1+3y)+5=13+5y | | 4.n=672 | | 7x+1.5=11.5 | | 120–5x=70 | | 179h-44=45 | | Y=60+1.6x | | 17x-(7x-6)=26 | | 9(4w−3)= | | 4m-19=-59 | | 9=9(a-9) | | 102=-6(64v-4)+6 | | 67=7+5x | | 5(x-1)+54=2x | | 4(y+17)=-72 | | 4(x+12)=-12 | | (x)/(4)-3=9 | | 5/y-7=3/y-5 | | 10-7/8x=17 | | 283=233-u | | 2(x-7)+2x=6x+5 | | 4/5x+3/10x=-3+7 | | -2x+5=35-4x |

Equations solver categories